The Impact of Work-Life Balance and Hybrid Work on Job Satisfaction: The Mediating Role of Music in the Workplace - Agung Rachmad Nuriyanto; Ronny Malavia Mardani; Nurhidayah Nurhidayah (International Journal of Management Science and Information Technology, 2026)
The modern workplace is currently undergoing a significant transformation driven by digitalization, where work is no longer confined to a fixed location or rigid schedule. The emergence of hybrid work systems has become an adaptive response by organizations, providing employees with greater opportunities to balance professional responsibilities and personal life (work-life balance). However, this flexibility also presents challenges, as the boundaries between professional and personal roles often become blurred, which may ultimately affect job satisfaction. In this context, music in the workplace emerges as a relevant supporting element, not only as background sound but also as a means to create a comfortable work atmosphere, enhance concentration, and maintain a positive mood. This study aims to examine the impact of work-life balance and hybrid work on job satisfaction, with music in the workplace positioned as a mediating variable. A quantitative approach was employed using survey data collected from hybrid workers, which were then analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to explore the relationships among variables. The findings indicate that well-maintained work-life balance and the effective implementation of hybrid work significantly improve job satisfaction. Furthermore, music in the workplace plays a mediating role that strengthens these relationships. Theoretically, this study contributes to the human resource management literature by highlighting the importance of psychological aspects in flexible work environments, while practically, it suggests that organizations should not only focus on flexibility but also consider employees’ emotional well-being to sustain job satisfaction.